Enhancing English Writing Skill through POEW Strategy - Ismu Laily Mufidah; Anita Rahma Dewi (TRANSBAHASA, 2021)
This research intended to explain the factors of students’ problems at eighth grade of SMP NU AlHidayah Maduran on English writing. It aimed to investigate the effect of POEW (Predict, Observe, Explain, Write) strategy used on English writing to enhance student’s English writing skill. In addition, it elaborated the significant after using POEW strategy on student’s narrative English writing. This research conducted using a quantitative design a quasi experimental research by two classes of pre-test and post-test. The researchers implemented this research to eighth grade of SMP NU Al Hidayah Maduran in academic year of 2021/2022. The participants of this study taken from eighth grade of SMP NU Al-Hidayah Maduran, which consisted of two classes and devided by experimental class and control class. It was found from the result of the test that students in experimental class got higher score than students in control class. However, based on the normality testing, this research was not normally distributed. In addition, the data declared that this research was not homogeneous. Thus, the researchers did Mann Whitney U Test. Relating to the test, the result of Asymp. Sig. (2-tailed) was smaller than the probability (0.000<0.05). It meant that Ha was accepted. However, it can be concluded that there was an effect of the use POEW strategy at eighth grade of SMP NU Al-Hidayah Maduran on English writing skill.